Analysis Of Leadership Behavior Factor Related To Work Expectations Through Organizational Commitment In Nurses - Suparman, Suparman; Ardiana, Anisah; Wijaya, Dodi; Susanto, Tantut; Prayitno, Hadi (Pusat Penelitian dan Pengabdian Masyarakat STIKES Banyuwangi, 2025)
Effective leadership behavior in hospitals can influence nurses’ performance, including job expectations. Positive job expectations can contribute to improving the quality of health services. In addition, organizational commitment is essential as a mediating factor that can connect leadership behavior with work expectations. However, this relationship has not been studied in depth in the context of hospitals. Therefore, this study aims to analyze the influence of leadership behavior on nurses’ work expectations through organizational commitment at Jember Lung Hospital. This study used a quantitative approach with a cross-sectional design. The total sample size was 146 nurses working at the Hospital of Paru in Jember. Data were collected using a questionnaire consisting of three questions: leadership behavior, organizational commitment, and work expectations. The data were analyzed using a logistic regression analysis to explore the influence between the variables studied. This study indicated that leadership behavior positively influences organizational commitment (p < 0.00). In addition, leadership behavior also has a positive effect on organizational commitment (p < 0.001). Organizational commitment mediates the relationship between leadership behavior and work expectations with a value (p < 0.00), which indicates that organizational commitment is a significant mediator in the process. The influence of mediation was 0.000, indicating a substantial contribution of mediation to work expectations. Positive leadership behavior can increase the commitment of nursing organizations and job expectations. This study suggests that hospital management needs to pay attention to leadership behavior to improve nurses’ motivation and work expectations, ultimately impacting the quality of health services.